Application of a novel enzymatic pretreatment using crude hydrolytic extracellular enzyme solution to microalgal biomass for dark fermentative hydrogen production - Yun, Yeo-Myeong; Kim, Dong-Hoon; Oh, You-Kwan; Shin, Hang-Sik; Jung, Kyung-Won (ELSEVIER SCI LTD, 2014)
In this study, a novel enzymatic pretreatment of Chlorella vulgaris for dark fermentative hydrogen production (DFHP) was performed using crude hydrolytic extracellular enzyme solution (CHEES) extracted from the H-2 fermented effluent of food waste. It was found that the enzyme extracted at 52 h had the highest hydrolysis efficiency of microalgal biomass, resulting in the highest H-2 yield of 43.1 mL H-2/g dry cell weight along with shorter lag periods. Even though a high amount of VFAs was accumulated in CHEES, especially butyrate, the fermentative bacteria on the DFHP was not affected from product inhibition. It also appears that the presence of organic acids, especially lactate and acetate, contained in the CHEES facilitated enhancement of H-2 production acted as a co-substrate. Therefore, all of the experimental results suggest that the enhancement of DFHP performance caused by CHEES has a dual role as the hydrolysis enhancer and the co-substrate supplier. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: WASTE-WATER; ENHANCEMENT; SUBSTRATE